2019
DOI: 10.4155/fmc-2018-0333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Structures and Cytotoxicity of Mupirocin and Batumin Against Melanoma and Several Other Cancer Cell Lines

Abstract: Aim: To determine the computer-predicted anticancer activity of mupirocin and to compare its activities with those determined for another polyene antibiotic, batumin. Materials & methods: Molecular docking, cytotoxicity assays, cell microscopy and cell cycle progression were studied in cancer and nontumorigenic cell lines. Results & conclusion: Cytotoxicity of mupirocin against several cancerous cell lines was detected with the highest one (IC50 = 5.4 μg/ml) against melanoma cell line. The profile of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Mupirocin has anti cancerous activity against the MCF-7 breast cancer cell line [ 40 ]. Like other inhibitors mupirocin was also docked with human ASNS, which showed that it binds with enzyme via hydrogen bonds (Asp261, Gly363, Glu443, Ser292, Asn478 and Trp480).…”
Section: Discussionmentioning
confidence: 99%
“…Mupirocin has anti cancerous activity against the MCF-7 breast cancer cell line [ 40 ]. Like other inhibitors mupirocin was also docked with human ASNS, which showed that it binds with enzyme via hydrogen bonds (Asp261, Gly363, Glu443, Ser292, Asn478 and Trp480).…”
Section: Discussionmentioning
confidence: 99%